A multi-criteria expert decision system for investment decisions: The case of commercial real estate investments in China. (September 2020) - Huang, Kun-Tai; Ozer, Muammer
Abstract: Consistent with the rapid growth of the Chinese economy and its commercial real estate (CRE) market, evaluating CRE investments in China is becoming an important application area where a multi-criteria expert decision system can make a significant contribution. We used a multi-criteria expert decision system to evaluate ten actual CRE investments in China. Based on thirty-one industry experts, we identified key decision factors to consider when evaluating different CRE investment projects and determined their importance weights. We then evaluated whether or not the ten CRE investment projects were considered to be successful, taking into account the unique characteristics of each CRE investment project. We finally compared the evaluations for the ten cases with their actual performance using four different performance indicators. The results showed that the evaluations had at least 87.5% accuracy across four different performance indicators. As probably one of the first systematic and in-depth scholarly studies to evaluate CRE investment projects in China, this study contributes to a better understanding of such evaluations and helps CRE investors evaluate CRE investment projects in a more informed fashion. Highlights: The commercial real estate (CRE) market is very important for the Chinese economy. A multi-criteria expert decision system is used to evaluate CRE investments in China. Expert identified key decision factors and determined their importance weights. The evaluations for ten CRE projects had at least 87.5% accuracy. This study contributes to a better understanding of the evaluation of CRE investments.